Canagliflozin and Heart Failure in Type 2 Diabetes Mellitus: Results From the CANVAS Program. Issue 5 (31st July 2018) - Rådholm, Karin; Figtree, Gemma; Perkovic, Vlado; Solomon, Scott D.; Mahaffey, Kenneth W.; de Zeeuw, Dick; Fulcher, Greg; Barrett, Terrance D.; Shaw, Wayne; Desai, Mehul; Matthews, David R.; Neal, Bruce
Abstract : Background: Canagliflozin is a sodium glucose cotransporter 2 inhibitor that reduces the risk of cardiovascular events. We report the effects on heart failure (HF) and cardiovascular death overall, in those with and without a baseline history of HF, and in other participant subgroups. Methods: The CANVAS Program (Canagliflozin Cardiovascular Assessment Study) enrolled 10 142 participants with type 2 diabetes mellitus and high cardiovascular risk. Participants were randomly assigned to canagliflozin or placebo and followed for a mean of 188 weeks. The primary end point for these analyses was adjudicated cardiovascular death or hospitalized HF. Results: Participants with a history of HF at baseline (14.4%) were more frequently women, white, and hypertensive and had a history of prior cardiovascular disease (all P <0.001). Greater proportions of these patients were using therapies such as blockers of the renin angiotensin aldosterone system, diuretics, and β-blockers at baseline (all P <0.001). Overall, cardiovascular death or hospitalized HF was reduced in those treated with canagliflozin compared with placebo (16.3 versus 20.8 per 1000 patient-years; hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.67–0.91), as was fatal or hospitalized HF (HR, 0.70; 95% CI, 0.55–0.89) and hospitalized HF alone (HR, 0.67; 95% CI, 0.52–0.87). The benefit on cardiovascular death or hospitalized HF may be greater in patients with a prior history of HF (HR, 0.61; 95% CI, 0.46–0.80) compared with those without HF at baseline (HR, 0.87; 95% CI, 0.72–1.06; P interaction =0.021). The effects of canagliflozin compared with placebo on other cardiovascular outcomes and key safety outcomes were similar in participants with and without HF at baseline (all interaction P values >0.130), except for a possibly reduced absolute rate of events attributable to osmotic diuresis among those with a prior history of HF ( P =0.03). Conclusions: In patients with type 2 diabetes mellitus and an elevated risk of cardiovascular disease, canagliflozin reduced the risk of cardiovascular death or hospitalized HF across a broad range of different patient subgroups. Benefits may be greater in those with a history of HF at baseline. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01032629 and NCT01989754. Abstract : Supplemental Digital Content is available in the text.